Sustaining the fleet, 1793-1815 war, the British Navy and the contractor state - Knight, Roger 1944-; Wilcox, Martin (Boydell Press, 2010)
Provisioning the fleet, and the army overseas, during the French Wars of 1793-1815 was a major undertaking. This book explains how the Victualling Board in London handled this enormous task, focusing in particular on contractors - that is the merchants and brokers, who provided a vast range of commodities including flour and biscuit, salt beef and pork, as well as huge quantities of fresh water and coal, and every other item needed. It shows how these merchants could be large or small concerns, and provides detailed case studies of different kinds of contractors, including examples of contractors based both in Britain and in the navy's overseas bases. The book demonstrates how, overall, the contracting system represented the mobilisation of a substantial part of the British economy for war; how the performance of contracting was effective, with little or no corruption; and how the contractors took considerable financial risks and made only reasonable margins. It assesses the performance of the Victualling Board, arguing that this was good, and that the problem in the major area of weakness - accounting - was quickly addressed following a major crisis in 1808-09. It concludes that this was "an impressive performance" by the state, but that the overwhelming advantage was the resilience of the market, and that it was "upon the success of the contractors that the war at sea was won." For most of his career, ROGER KNIGHT was on the staff of the National Maritime Museum, leaving as Deputy Director in 2000. Since then he has taught at the Greenwich Maritime Institute at the University of Greenwich, where he is currently Visiting Professor of Naval History
Title from publisher's bibliographic system (viewed on 01 Mar 2023)
Keywords: Great Britain / Victualling Office / History; Great Britain / Royal Navy / Provisioning / History / 18th century; Great Britain / Royal Navy / Provisioning / History / 19th century; Defense contracts / Great Britain / History / 18th century; Defense contracts / Great Britain / History / 19th century; Great Britain / History, Naval / 18th century; Great Britain / History, Naval / 19th century